Logistics Development in the Light of Systems Thinking Paradigm (Economic and Political Thought, 2013)
Logistics is a new discipline of management. During the last decades itsgrowth has been very dynamic. The thesis proposed in this paper states thatlogistics develops in the direction of systems thinking paradigm. To justify thisstatement, the main systems thinking assumptions have been presented; thedefinition of logistics, its military history and three main phases of logisticsdevelopment: non-integrated logistics, supply chain and networks have alsobeen described. Although, because of its nature, logistics should be perceivedand managed as a system, it has not always been the rule. The conclusion ofthis paper is that the more advanced the logistics evolution phase, the moresystem oriented its management.